Enhancing Reliability in LEO Satellite Networks via High-Speed Inter-Satellite Links - Choi, Jinho (IEEE wireless communications letters, 2024)
Low Earth orbit (LEO) satellites play a crucial role in providing global connectivity for non-terrestrial networks (NTNs) and supporting various Internet-of-Remote-Things (IoRT) applications. Each LEO satellite functions as a relay node in the sky, employing store-and-forward transmission strategies that necessitate the use of buffers. However, due to the finite size of these buffers, occurrences of buffer overflow leading to packet loss are inevitable. In this letter, we demonstrate how inter-satellite links (ISLs) can mitigate the probability of buffer overflow. Specifically, we propose an approach to reallocate packets among LEO satellites via ISLs to minimize the occurrence of buffer overflow events. Consequently, the implementation of ISLs can lead to a more reliable satellite network, enabling efficient packet reallocation to reduce the probability of buffer overflow.